Pembentukan Karakter dan Etika Anak-Anak Melalui Kegiatan KKN Berbasis Nilai-Nilai Lokal di Kampung Banjar 1 Kota Pinang - Juni Ariansyah Pulungan; Azzuhro Azzuhro; Arfani Rahman Sari; Jufri Naldo (FKIP, Universitas Palangka Raya, 2024)
This study aims to describe how the character and ethics of children are formed through KKN activities held by the State Islamic University of North Sumatra. This research is a descriptive qualitative research using data collection techniques in the form of interviews, observation, and documentation. The formation of children's character and ethics is very important to be formed from an early age. Accustoming children to being honest is an example of a small thing that children in Kampung Banjar 1 Kotapinang have to get used to. With the presence of North Sumatra State Islamic University KKN students in South LabuhanBatu district, they can create little by little changes regarding the character building and ethics of children in Kampung Banjar 1 Kotapinang. By utilizing existing local values, students participate in guiding and directing children to continue to carry out positive activities.